If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x(2x + 6)(x + -1) = 0 Reorder the terms: 3x(6 + 2x)(x + -1) = 0 Reorder the terms: 3x(6 + 2x)(-1 + x) = 0 Multiply (6 + 2x) * (-1 + x) 3x(6(-1 + x) + 2x * (-1 + x)) = 0 3x((-1 * 6 + x * 6) + 2x * (-1 + x)) = 0 3x((-6 + 6x) + 2x * (-1 + x)) = 0 3x(-6 + 6x + (-1 * 2x + x * 2x)) = 0 3x(-6 + 6x + (-2x + 2x2)) = 0 Combine like terms: 6x + -2x = 4x 3x(-6 + 4x + 2x2) = 0 (-6 * 3x + 4x * 3x + 2x2 * 3x) = 0 (-18x + 12x2 + 6x3) = 0 Solving -18x + 12x2 + 6x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '6x'. 6x(-3 + 2x + x2) = 0 Factor a trinomial. 6x((-3 + -1x)(1 + -1x)) = 0 Ignore the factor 6.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-3 + -1x)' equal to zero and attempt to solve: Simplifying -3 + -1x = 0 Solving -3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 0 + 3 -1x = 0 + 3 Combine like terms: 0 + 3 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3Subproblem 3
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Solution
x = {0, -3, 1}
| 1+2(3n-1)=5 | | 13x-21-7=-63 | | p(p-2)=24 | | 4x^2-296x+85= | | 5w(4w+3)=-8w-6 | | 6s^2-5-29s=0 | | m(m-11)=-30 | | 2v^2-2-3v=0 | | 20x+40y=10 | | x^4+3x^3-10x^2=0 | | 6w^3+17w^2+12w=0 | | p^2=-12p | | m^2=-3m+10 | | 3x^5+3x-24=0 | | x^3-3x^2+3x=0 | | 12a+4a+3a+6a= | | 6x^3-1x^2-12x=0 | | k=3+2b | | 20x^3-19x^2+3x=0 | | p^3-4p=0 | | 8x+22=6x+74 | | 4x^2-19x+21=-2x+3 | | m^3-100=0 | | 212-2x=34x+20 | | x^2-3=-3x+1 | | 4x+6=134-10x | | m^2=19m-88 | | -[2x+(6x+3)]= | | x^2-12x-43=-5x-1 | | 15x^2+32x-7=0 | | 2-(4x+7)= | | 2x+38=11x+52 |